Android-Based Instructional Multimedia for Food Ingredients Knowledge: A Development Study in Culinary Vocational Education - Taswin Rahmat; Abdul Muis Mappalotteng; Muhammad Yusuf Mappeasse (PT. Global Research Collaboration, 2026)
Background/Context:.The rapid development of digital technology has expanded learning opportunities through interactive multimedia. However, learning practices in vocational schools are still dominated by conventional methods with limited use of innovative media, resulting in low student motivation and engagement, particularly in the Food Materials Knowledge subject. Objective/Purpose: This study aimed to develop Android-based multimedia learning media and examine its validity, practicality, effectiveness, and impact on students’ learning outcomes and motivation. Method: The research employed a Research and Development approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The product was validated by subject matter experts and media experts, followed by individual trials, small group trials, and field testing with Grade X Culinary Arts students. Data were collected through questionnaires, observations, and pre-test and post-test assessments. Results: Expert validation indicated that the developed multimedia was in the excellent category. Practicality testing showed very positive student responses, with a high feasibility score. Effectiveness testing revealed a significant improvement in learning outcomes, with the average post-test score increasing substantially compared to the pre-test and an N-gain value in the high category. Conclusion: The Android-based multimedia learning media is valid, practical, and effective in enhancing student engagement and learning outcomes in vocational food science education, and it can serve as an innovative learning tool to support interactive classroom instruction